2011
DOI: 10.1002/ajmg.a.34128
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement from the first international colloquium on basal cell nevus syndrome (BCNS)

Abstract: The first international colloquium on basal cell nevus syndrome (BCNS) was held at Saint Louis University School of Medicine and supported by the Basal Cell Carcinoma Nevus Syndrome (BCCNS) Life Support Network (www.gorlinsyndrome.org). The foremost goal of the conference was to review and revise the prior diagnostic criteria and define the surveillance recommendations for affected pediatric and adult patients to allow for early intervention. The invited consensus group participants included geneticists, derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
198
1
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(229 citation statements)
references
References 11 publications
(14 reference statements)
4
198
1
26
Order By: Relevance
“…NBCCS (Gorlin syndrome) is an autosomal-dominantly inherited syndrome characterized by several major clinical features including multiple basal cell carcinomas (BCCs), multiple OKCs, palmar or plantar pitting, and intracranial calcification [5,6]. The causative mutations have been found to be in the sonic hedgehog pathway, including PTCH1 [22,23], PTCH2 [24], and SUFU [25], with PTCH1 mutation being found in 60-75 % of NBCCS patients [6,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NBCCS (Gorlin syndrome) is an autosomal-dominantly inherited syndrome characterized by several major clinical features including multiple basal cell carcinomas (BCCs), multiple OKCs, palmar or plantar pitting, and intracranial calcification [5,6]. The causative mutations have been found to be in the sonic hedgehog pathway, including PTCH1 [22,23], PTCH2 [24], and SUFU [25], with PTCH1 mutation being found in 60-75 % of NBCCS patients [6,26].…”
Section: Discussionmentioning
confidence: 99%
“…The causative mutations have been found to be in the sonic hedgehog pathway, including PTCH1 [22,23], PTCH2 [24], and SUFU [25], with PTCH1 mutation being found in 60-75 % of NBCCS patients [6,26]. Although it is a genetic disease, about 35-50 % of affected patients represent new mutations [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exonic, multiexonic, and whole-gene deletions have been reported in about 6% of individuals with NBCCS [Evans and Farndon, 2002]. The studies of disease prevalence come from the UK population, where it is nearer to 1:30,827 [Evans et al, 2010]; The actual figure could be higher still, since less severe cases may not be diagnosed and Jones et al [2011] recently reported an incidence of 1 in 19,000 births.NBCCS is clinically diagnosed in patients with one major diagnostic criterion and molecular confirmation or two major criteria or one major and two minor diagnostic criteria [Bree et al, 2011]. The major criteria are the following: (1) BCC before the age of 20 or excessive numbers of BBCs out of proportion to prior sun exposure and skin type, (2) odontogenic jaw keratocyst prior to 20 years of age, (3) palmar or plantar pitting, (4) lamellar calcification of the falx cerebri, (5) medulloblastoma typically desmoplastic, and (6) first-degree relative with NBCCS.…”
mentioning
confidence: 99%